2013
DOI: 10.4236/ojanes.2013.35063
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Imaging of the Sciatic Nerve Division in the Popliteal Fossa: A Volunteer Study

Abstract: The Background and Objectives: A sciatic nerve block at the level of the popliteal fossa is frequently administered for post-operative analgesia for surgery below the knee. While ultrasound continues to gain popularity as the technique of choice for guiding needle positioning during peripheral nerve blocks, practitioners can begin to utilize ultrasound to look for patterns of anatomical significance. Recognizing anatomical variations among different demographic populations can help practitioners improve in per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 15 publications
1
4
1
Order By: Relevance
“…Our finding correlates with the study by Chiang et al where the mean distance of SN bifurcation was 5.77 cm and 6.02 cm for the females and males respectively. 11 Similar was the finding by Vloka et al and this cadaveric study showed that SN divided at 6.05 ± 2.70 cm from the popliteal crease. 9 The lesson to take away is that these distances varied greatly, from 0 to 11.5 cm, and that too in a small number of cadavers.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our finding correlates with the study by Chiang et al where the mean distance of SN bifurcation was 5.77 cm and 6.02 cm for the females and males respectively. 11 Similar was the finding by Vloka et al and this cadaveric study showed that SN divided at 6.05 ± 2.70 cm from the popliteal crease. 9 The lesson to take away is that these distances varied greatly, from 0 to 11.5 cm, and that too in a small number of cadavers.…”
Section: Discussionsupporting
confidence: 90%
“…Chiang et al have stated in their study that 28% of their volunteers had more than 2 cm difference in the crease to nerve distance in their right and left legs and have expressed concern this difference could be significant if an extra-epineural injection is performed and there could be an incomplete block. 11 Our study has shown that this variation of more than 2 cm between limbs of the same individual is only 8.25%, less than the study by Chiang et al 11 The same study also found a predictable variability in the depth of bifurcation of sciatic nerve at the popliteal fossa and found consistent deeper skin depth values for female patients than males, 0.4 cm to be exact. Our study strengthens this view because our data shows that women have greater mean skin-nerve distances than men.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…The sciatic nerve block in the popliteal fossa is frequently administered for anesthesia and postoperative pain blockage for lower extremity surgery below the knee. The sciatic nerve division in the popliteal fossa and its depth have significant implications for popliteal block (7,(15)(16)(17). Vloka et al (15) suggested that insertion of the needle at 100 mm above the popliteal crease was most suitable placement, as a different opinion according to the classical teaching.…”
Section: Discussionmentioning
confidence: 99%
“…The division of the sciatic nerve may occur anywhere from the sacral plexus to the popliteal fossa. Some anatomical variations concerning its topography and division such as the division of the sciatic nerve in the popliteal fossa may be also responsible for failure of sciatic nerve popliteal blocks (10,15,16,17).…”
Section: Introductionmentioning
confidence: 99%